2022
DOI: 10.1007/s13762-022-04261-1
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in environment: global concern, challenges, and controlling measures

Abstract: Plastic pollution in various forms has emerged as the most severe environmental threat. Small plastic chunks, such as microplastics and nanoplastics derived from primary and secondary sources, are a major concern worldwide due to their adverse effects on the environment and public health. Several years have been spent developing robust spectroscopic techniques that should be considered top-notch; however, researchers are still trying to find efficient and straightforward methods for the analysis of microplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(32 citation statements)
references
References 164 publications
(166 reference statements)
0
31
0
1
Order By: Relevance
“…MNPs can be classified into two types based on their source of origin: primary MNPs originate from pre-production plastic pellets in manufacturing industries, scrubbers, plastic resin flakes, plastic powder, commercial cleaning abrasives, or fluff used to produce plastic goods [ 37 ]. Secondary MNPs originate from the breakdown of larger plastic materials [ 38 ], and the frequency of fragmentation depends on the environmental conditions. MNPs penetrate the environment through land-based sources, atmospheric deposition, air transportation, textiles, and aquaculture ( Figure 2 ).…”
Section: Environmental Contaminants: Plastics In the Environmentmentioning
confidence: 99%
“…MNPs can be classified into two types based on their source of origin: primary MNPs originate from pre-production plastic pellets in manufacturing industries, scrubbers, plastic resin flakes, plastic powder, commercial cleaning abrasives, or fluff used to produce plastic goods [ 37 ]. Secondary MNPs originate from the breakdown of larger plastic materials [ 38 ], and the frequency of fragmentation depends on the environmental conditions. MNPs penetrate the environment through land-based sources, atmospheric deposition, air transportation, textiles, and aquaculture ( Figure 2 ).…”
Section: Environmental Contaminants: Plastics In the Environmentmentioning
confidence: 99%
“…Nanoscale microplastics can lead to the creation of Reactive Oxygen Species (ROS), suggesting that they may cause stress to cells by promoting oxidative reactions (Campanale et al, 2020; Paul et al, 2020; Yee et al, 2021). Concurrent inflammatory responses may destabilize cellular homeostasis, possibly marking the onset of apoptosis (Elmore, 2007; Lamichhane et al, 2023; Wright et al, 2013). There could also be direct physical effects, such as potential damage or blockages in tissues, especially in organisms with multiple cell types (Bhagat et al, 2021; Yee et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have further identified fibers as particularly ecologically harmful (see recent reviews by Singh et al, 96 Lamichhane et al, 97 and Mason et al 82 ), though it remains unclear if microfiber toxicity is driven by this specific morphology causing physical entanglement, or if the chemical composition of the respective plastics includes harmful additives. Face mask fragments, which were primarily polypropylene (Supplemental Information Figure S-1), induced a 65% reduction in the final population of L. variegatus relative to the control after 30 days (t = 5.9, df = 7.6, p = 0.011; Figure 1A).…”
Section: Resultsmentioning
confidence: 99%